2020
DOI: 10.3390/brainsci10010034
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Deep Brain Stimulation and Its Earlier Use for Parkinson’s Disease: A Qualitative Study of US Patients

Abstract: Background: Deep brain stimulation (DBS) is being used earlier than was previously the case in the disease progression in people with Parkinson’s disease (PD). To explore preferences about the timing of DBS, we asked PD patients with DBS whether they would have preferred the implantation procedure to have occurred earlier after diagnosis. Methods: Twenty Michigan-based patients were interviewed about both their experiences with DBS as well as their attitudes regarding the possible earlier use of DBS. We used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Two prevailing motivations for enrollment in the early DBS trial arose in this study: (1) desire to help future PD patients by participating in research and (2) potential benefits of early DBS (i.e., maintaining careers and independence, preventing disability, and slowing disease progression). Prior studies investigating whether standard-of-care DBS patients would have preferred earlier DBS similarly cited slowing progression and regaining freedoms sooner as motivators, with the additional motivation of eliminating medication side effects earlier [ 27 ]. In contrast, key motivators for patients considering standard-of-care DBS include their worsening symptoms, family encouragement, and confidence in the recommendation of the physician [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prevailing motivations for enrollment in the early DBS trial arose in this study: (1) desire to help future PD patients by participating in research and (2) potential benefits of early DBS (i.e., maintaining careers and independence, preventing disability, and slowing disease progression). Prior studies investigating whether standard-of-care DBS patients would have preferred earlier DBS similarly cited slowing progression and regaining freedoms sooner as motivators, with the additional motivation of eliminating medication side effects earlier [ 27 ]. In contrast, key motivators for patients considering standard-of-care DBS include their worsening symptoms, family encouragement, and confidence in the recommendation of the physician [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This concern is likely to carry even greater weight in a population considering early DBS, as patients are still functioning well and do not yet see DBS as a last resort. While some PD patients certainly express hesitation to consider early DBS [ 27 ], there is a notable proportion of patients who indicate that the potential benefits may outweigh the risks [ 27 , 29 , 30 , 31 ]. Currently, early DBS is appropriately only offered in research studies, and a pivotal safety and efficacy study is needed to understand if DBS should be offered earlier in Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…If replicated, knowledge of survival benefits related to DBS surgery at an earlier age may narrow widespread clinician and patient perspectives regarding the earlier use of DBS for PD. 33,34 Randomized controlled trials (RCTs) and observational studies have examined differences in the risk of falling between PD patients treated with DBS or best medical therapy. One RCT found that DBS recipients (n = 121) were significantly more likely to experience injurious falls within 6 months of randomization than patients in the best medical therapy group (n = 134).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results of qualitative studies are of great interest for neurologists and other clinicians as they serve to better understand the patients’ needs and tailor individualized treatment (e.g., choosing between DBS or medical pumps to treat motor fluctuations and dyskinesias). The available qualitative studies in the field have typically focused either on specific aspects of PD [ 40 , 41 , 42 ], the perception of DBS [ 38 , 43 ], or some side effects of DBS affecting patients’ personality or identity [ 44 , 45 , 46 ]. However, there are few studies with a comprehensive approach encompassing the patients’ experiences with both PD and DBS and deepening their perception of both [ 37 , 47 ].…”
Section: Introductionmentioning
confidence: 99%